PEMBELAJARAN MENULIS ISU DAN OPINI TEKS DISKUSI BERBASIS MODEL MODIFIKASI TSTS - Sudarsri Lestari; Erisy Syawiril Ammah; Rima Trianingsih (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
This study aims to examine learning to write issues and opinions on discussion texts for junior high school students based on the modified TSTS model. A quasi-experimental research design is used with an unequal control group design (Sugiono, 2012). This research method is carried out by looking at the pretest (pretest) and posttest (posttest) scores on writing issues and opinions on discussion texts. The research findings, namely (1) there is a significant effect of the modified TSTS learning model on learning to write discussion text issues and (2) there is a significant effect of the TSTS modified learning model on learning to write discussion text opinions. The results of the findings of this study are suggested to be used to support the practice of learning to write discussion texts in schools.